2012
DOI: 10.1002/brb3.40
|View full text |Cite
|
Sign up to set email alerts
|

Progression of leprosy neuropathy: a case series study

Abstract: A need still exists to determine the clinical and neurophysiological characteristics of leprosy neuropathy at distinct times of the disease by different methods that measure the various nerve fiber functions. A prospective clinical study was performed with 10 paucibacillary (PB) and 12 multibacillary (MB) patients evaluated at diagnosis and one year after cessation of multidrug therapy (MDT). Peripheral nerve function was assessed clinically and by means of the sympathetic skin response, skin vasomotor reflex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 18 publications
(32 reference statements)
3
36
0
Order By: Relevance
“…Disability was recorded in accordance with the standard WHO grading criteria [46]. NFI was defined as clinically detectable impairment of the motor, sensory, and/or autonomic functions [41]. Table 1 Upper/lower limits values for the sensory and motor nerves evaluated [14,17,24,32].…”
Section: Methodsmentioning
confidence: 99%
“…Disability was recorded in accordance with the standard WHO grading criteria [46]. NFI was defined as clinically detectable impairment of the motor, sensory, and/or autonomic functions [41]. Table 1 Upper/lower limits values for the sensory and motor nerves evaluated [14,17,24,32].…”
Section: Methodsmentioning
confidence: 99%
“…In 396 new cases that included all forms of leprosy, van Brakel and Khawas observed that, in the upper extremities, the ulnar nerve was the most frequently affected, both in its motor (20%) and sensory components (17%), whereas the median sensory nerve was only affected in 8.8% of the cases. Other investigators have also observed the median nerve to be the least compromised in the upper extremities, but it was always associated with impairment of other nerves. We have reported here a rare presentation of leprosy in which median neuropathy was the first symptom of the disease.…”
Section: Discussionmentioning
confidence: 89%
“…A detailed neurological examination was performed to record the number and distribution of affected nerves. To define nerve function impairment (NFI) the following components were analyzed according to Vital et al …”
Section: Methodsmentioning
confidence: 99%
“…57 It may also worsen in the presence of reactions. 58 Small fiber neuropathy (SFN) is also reported in patients with leprosy, with a pattern of distal loss of sensitivity to temperature and pain. Thickening of nerves can be seen; one small study found this in about half of patients with SFN attributed to leprosy.…”
Section: Neurological Manifestationsmentioning
confidence: 99%